Is the Risk of Preeclampsia Higher in Donor Oocyte Pregnancies? a Systematic Review and Meta-Analysis - Schwarze-Meza, J (Sociedade Brasileira de Reproducao Assistida, 2018)
Objective: Preeclampsia (PE) occurs in 4.6% of pregnancies worldwide. The social phenomenon of increasing maternal age has raised the demand for donor oocytes. Egg donation has allowed women with poor ovarian reserve, premature ovarian failure, genetic disorders or surgical menopause to get pregnant. Recipients provide a unique model of immune response because of the differences in the genetic makeup of mothers and fetuses. In PE, immune tolerance may be impaired as a result of having non-autologous eggs implanted. Egg donation is a highly successful assisted reproductive technology, despite the significant number of issues arising from the implantation of non-autologous eggs. This study aimed to determine whether there is an association between egg donation and preeclampsia. Methods: A systematic review of the literature available in PubMed and Google Scholar was carried out from January of 1995 to August of 2016 using the terms oocyte donation, preeclampsia , oocyte donation, in vitro fertilization, preeclampsia , oocyte donation, preeclampsia, outcomes pregnancies , oocyte donation, obstetric outcome. Only six retrospective cohort studies met the selection criteria. Result: The meta-analysis revealed a statistically significant association between egg donation and onset of preeclampsia (OR 4.50; 95% CI: 3.28-6.19; p<0.0001). Conclusion: Oocyte donation is associated with increased risk of preeclampsia in singleton pregnancies. Therefore, it is crucial to properly record and assess this finding when egg donation is the chosen assisted reproductive technology to attain pregnancy. © 2018, Sociedade Brasileira de Reproducao Assistida. All rights reserved.